Geneza Praskiej Wiosny (Czechosłowacja w latach 1948-1966) - Kwapis, Robert (Acta Universitatis Lodziensis. Folia Historica, 1999)
The reasons of the Spring of Prague - those dramatic events in Czechoslovakia in the years 1968-1969 - were gradually cumulating during whole twenty years, from February 1948, when Communist Party of Czechoslovakia had taken an undivided control over the country. Three main areas of quarrels between the communist government and the society were crystallised at the end of 1966. There were the problems connected with the model of economic development of the country, the questions of the civil liberties (especially the freedom of speech), and of the relations between the Czech and the Slovak people. The intelligentsia was a spiritus movens of the changes in Czechoslovakia. The opposition aimed at a creation of a better model of the socialistic state by introducing some economic reforms, democratisation of the political system and the civil liberties as well as the participation of the citizens in the governing of the country. They assumed, that such a model of socialism would be able to regain the support of the society and awake the activity of the people.